Minimally invasive distal first metatarsal osteotomy can be an option for recurrent hallux valgus. Issue 3 (June 2019) - Magnan, Bruno; Negri, Stefano; Maluta, Tommaso; Dall'Oca, Carlo; Samaila, Elena
Highlights: Hallux valgus revision surgery is burdened by high incidence of complications. Looking for new alternatives among minimally invasive surgery could be reasonable. PDO can be an option addressing most of anatomical features of the deformity. Results are similar to traditional procedures with lower complications. Abstract: Background: Recurrence rate of surgical treatment of hallux valgus ranges in the literature from 2.7% to 16%, regardless of used procedure. In this study, long-term results of a minimally invasive distal osteotomy of the first metatarsal bone for treatment of recurrent hallux valgus are described. Methods: 32 consecutive percutaneous distal osteotomies of the first metatarsal were performed in 26 patients for treatment of recurrent hallux valgus. Primary surgery had been soft tissue procedures in 8 cases (25%), first metatarsal or phalangeal osteotomies in 19 cases (59.4%) and Keller procedures in 5 cases (15.6%). Results: Patients were assessed with a mean follow-up of 9.8 ± 4.3 years. All patients reported the disappearance or reduction of the pain. The mean overall AOFAS score improved from 46.9 ± 17.8 points to 85.2 ± 14.9 at final follow-up. The mean hallux valgus angle decreased from 26.1 ± 9.1 to 9.7 ± 5.4°, the intermetatarsal angle decreased from 11.5 ± 4.5 to 6.7 ± 4.0°. No major complications were recorded with a re-recurrence rate of 3.1% (1 case). Conclusions: Percutaneous distal osteotomy of the first metatarsal can be a reliable and safe surgical option in the recurrent hallux valgus with low complication rate and the advantages of a minimally invasive surgery. Levels of evidence: : IV, Retrospective Case Series.